2009
DOI: 10.1007/s11661-009-9881-6
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Fundamental Relationships between Deformation-Induced Surface Roughness and Strain Localization in AA5754

Abstract: Three-dimensional, matrix-based statistical analysis methods were developed and integrated with high-resolution topographical imaging, to assess how microstructural changes influence the evolution of plastic deformation and strain localization in a commercial AA5754-O aluminum sheet in three in-plane strain modes. Analysis of the raw surface data revealed that the general composition of the surface roughness was highly sensitive to strain mode and strain level. The microstructural conditions that promote strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 42 publications
2
23
0
Order By: Relevance
“…As shown previously, raw topographic data have a character that can generally be described with Gaussian statistics. [6,15,21,22] This is convenient since Rq is defined as one standard deviation of the normal distribution (i.e., Rq " r). [23,24] Even though it is more common in the surface roughness literature, Ra has no definitional association to the moments of the height distribution.…”
Section: A Evaluation Of Surface Roughness Datamentioning
confidence: 99%
“…As shown previously, raw topographic data have a character that can generally be described with Gaussian statistics. [6,15,21,22] This is convenient since Rq is defined as one standard deviation of the normal distribution (i.e., Rq " r). [23,24] Even though it is more common in the surface roughness literature, Ra has no definitional association to the moments of the height distribution.…”
Section: A Evaluation Of Surface Roughness Datamentioning
confidence: 99%
“…This section is a synopsis of the procedures presented in [11] that were used to generate surface data in the various strain conditions. Sets of 30 Â 30 cm (12 Â 12 in) blanks were sheared from 1-mm thick commercially available AA5754-O sheet stock for testing.…”
Section: Generation and Evaluation Of Surface Roughnessmentioning
confidence: 99%
“…This paper is one in a series documenting analyses of strain localisation behaviour in commercial aluminium sheet [11][12][13]. The inspiration for this research is derived from the work of Frost and Ashby [14], and others [15,16], in that changes in the microstructure or, in this case, surface morphology, can be 'mapped' with respect to the level of plastic deformation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wilson et al (1983) found a non-linear relationship of surface roughness to strain at large strains. Stoudt et al (2009) were also skeptical of data from models assuming linear relationships between surface roughness and plastic strain. Objecting to the use of linear profiles on the assessment of roughening behavior, they proposed a statistical model based on Weibull distributions instead.…”
Section: Introductionmentioning
confidence: 99%